IMPLEMENTASI KEBIJAKAN STANDAR PELAYANAN MINIMAL PENDERITA DIABETES MELLITUS DI PUSKESMAS PANDANARAN KOTA SEMARANG - Rahmadani, Annisa Nurindra; Surjoputro, Antono; Budiyanti, Rani Tiyas (Jurnal Kesehatan Masyarakat (Undip), 2021)
Diabetes mellitus (DM) is the fifth most disease in Semarang, but the achievement of Minimum Service Standard (SPM) only reached 50.64% in 2017. The district with the highest morbidity in Semarang is South Semarang which has two health centers. Puskesmas Pandanaran has lower achievement than the other central health in South Semarang, which is 89%. The purpose of this study is to analyze the implementation of SPM for DM in Puskesmas Pandanaran. The research method is qualitative research with in-depth interviews. Research subjects include the head of puskesmas, the program in charge, the program implementer, and the community. The research was conducted in August-October 2020. The results showed that the implementation of SPM services is still constrained at the stage of logging and early detection of DM patients. Unfulfilled performance targets are affected by standard and policy objectives that are difficult to achieve due to differences in the amount of target with the actual population, lack of infrastructure resources and funding sources, there is no Standar Operational Procedure (SOP) in the implementation of SPM for DM patients, and community knowledge factors. The conclusion of this study is variable that affects the performance of SPM are standards and policy objectives, resources, characteristics of implementing organizations and the social environment of the community. Coordination between health services and health centers regarding the use of data as targets for achievement is required, addition and fulfillment of infrastructure and funds, creating SOPs, forming team to record DM patients, and giving education.